2016
DOI: 10.1007/s00330-016-4622-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Parkinsonism Index: diagnostic accuracy of a fully automated algorithm in comparison with the manual measurement in a large Italian multicentre study in patients with progressive supranuclear palsy

Abstract: • A new automatic method for calculating the MRPI is presented. • Automatic MRPI values are in good agreement with manual values. • Automatic MRPI can distinguish patients with PSP from patients with PD. • The automatic method overcomes MRPI application limitations in routine practice. • The automatic method may allow a more widespread use of MRPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 28 publications
5
84
1
1
Order By: Relevance
“…Consistent with our previous data, in the current study no patients with initial diagnosis of PD showed abnormal morphometric MR measurements (P/M 2.0, MRPI, and MRPI 2.0) at baseline evaluation in comparison with controls with the exception of P/M, which showed higher values in PD than in controls, a finding probably a result of the slight reduction of the midbrain area that may be observed in PD patients …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our previous data, in the current study no patients with initial diagnosis of PD showed abnormal morphometric MR measurements (P/M 2.0, MRPI, and MRPI 2.0) at baseline evaluation in comparison with controls with the exception of P/M, which showed higher values in PD than in controls, a finding probably a result of the slight reduction of the midbrain area that may be observed in PD patients …”
Section: Discussionsupporting
confidence: 93%
“…However, the use of MRPI in clinical practice has been limited because the manual calculation of this combined measurement is operator dependent and time consuming. A large multicenter study in Italy recently introduced a new accurate fully automated method for MRPI calculation that does not require the manual segmentation of brain regions involved in the calculation of the index …”
Section: Discussionmentioning
confidence: 95%
“…We studied the MRPI in 81 patients who were clinically uncertain parkinsonism (including 15 patients who developed PSP and 11 patients who developed MSA) due to their early disease stage and found that an abnormal MRPI predicts PSP with a diagnostic accuracy of 85% (unpublished data). Very recently, an automated method for the MRPI calculation has been established and validated in a large cohort of 88 patients with clinically established PSP, 234 PD patients and 117 controls showing a diagnostic accuracy of 95% in separating PSP from PD (Nigro et al 2016). …”
Section: Exclusion Of Alternative Diagnosesmentioning
confidence: 99%
“…Quattrone and Nigro for their thoughtful comments concerning MRI measures in neurodegenerative parkinsonism. We fully agree that automated MRI analysis algorithms may be advantageous over the manual analysis for the same planimetric and volumetric MRI parameters, as investigated for the MR Parkinsonism Index (MRPI) in the Italian multicenter cohort . However, the past literature still remained controversial with regard to the question as to which parameter should be measured (e.g., a.p.…”
mentioning
confidence: 60%
“…A direct cross‐study comparison for the performance of one specific measurement parameter, even by use of different technical approaches, has necessarily to be hampered by study‐specific characteristics, that is, differences in the cohorts, diagnostic criteria, disease stages, and imaging acquisition standards. For example, the study samples of the German multicenter PSP cohort differed, on average, by 0.85 years shorter disease duration and 8.2 points less in the UPDRS‐III from the Italian multicenter PSP cohort, so that it is not at all surprising that the cohort with the more advanced PSP patients yielded higher diagnostic certainty. This variability in the performance of neuroimaging measurements, when applied to different study populations, has been emphasized in the current systematic review on neuroimaging in PSP by the MDS‐endorsed PSP Study Group .…”
mentioning
confidence: 99%